Financial Performance Analysis BUMN Banks and Private Foreign Exchange Banks Go Public on the IDX - Rian Risendy; Suryadi Samudra (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
Bank is one of the financial institutions that have an important role in the economy of a country as a financial intermediary institution. Banks can be said to be the blood of a country's economy. Therefore the progress of a bank in a country can also be used as a measure of the progress of the country concerned. The more advanced a country is, the greater the role of banks in controlling the country, meaning that the existence of the banking world is increasingly needed by the government and society. For this role, an assessment tool for bank health is needed using the existing financial ratio approach. This study uses the measurement of banking financial ratios, namely the profitability ratio ( earning ratios), liquidity ratios (liquidity ratios), and solvency ratios (capital ratios).